Getting Your Scholarly Papers Published: A Guide on How to Avoid the Top Ten Most Common Causes of Paper Rejection - Adom, Dickson (Journal of Academic Writing, 2024)
Scholarly writing and publishing are activities marked by intellectual honesty, integrity, and excellence. Together, they are an indispensable requirement for academics to maintain and sustain their careers in various academic institutions. However, in higher education institutions, the infamous aphorism 'publish or perish' has resulted in unethical academic practices. These practices derail the quality expected of scholarly writing and publishing. This paper is a collection of advice to novice writers on the ten most common reasons why scholarly papers are rejected, offering sound solutions to these problems. Though an unpleasant experience, scholarly paper rejection keeps authors on guard against unethical academic writing practices. It helps them to transform their scholarly papers to meet the high standards of academia. The paper contends that scholarly paper rejection is an important activity in scholarly writing and publishing because it ensures quality in academic knowledge production and dissemination.